Effects of Immunonutrition in Advanced Human Immunodeficiency Virus Disease: A Randomized Placebo-controlled Clinical Trial (Promaltia Study). (16th May 2018) - Serrano-Villar, Sergio; de Lagarde, María; Vázquez-Castellanos, Jorge; Vallejo, Alejandro; Bernadino, José I; Madrid, Nadia; Matarranz, Mariano; Díaz-Santiago, Alberto; Gutiérrez, Carolina; Cabello, Alfonso; Villar-García, Judit; Blanco, José Ramón; et al.
Abstract : After 48 weeks of immunonutrition in HIV-infected individuals starting antiretroviral therapy at advanced disease, most of the T-cell, inflammation, and bacterial translocation markers improved similarly in the active and control groups. Abstract: Background: While nutritional interventions with prebiotics and probiotics seem to exert immunological effects, their clinical implications in human immunodeficiency virus (HIV)–infected subjects initiating antiretroviral therapy (ART) at advanced HIV disease remain unclear. Methods: This was a pilot multicenter randomized, placebo-controlled, double-blind study in which 78 HIV-infected, ART-naive subjects with <350 CD4 T cells/μL or AIDS were randomized to either daily PMT25341 (a mixture of synbiotics, omega-3/6 fatty acids and amino acids) or placebo for 48 weeks, each in combination with first-line ART. Primary endpoints were changes in CD4 T-cell counts and CD4/CD8 ratio from baseline to week 48 and safety. Secondary endpoints were changes in markers of T-cell activation, bacterial translocation, inflammation, and α and β microbiota diversity. Results: Fifty-nine participants completed the follow-up with a mean CD4 + T-cell count of 221 ± 108 cells/μL and mean CD4/CD8 ratio of 0.26 ± 0.19. PMT25341 was well tolerated, without grade 3–4 adverse effects attributable to the intervention. While most of the assessed biomarkers improved during the follow-up in both arms, PMT25341-treated subjects did not experience any significant change, compared to placebo-treated subjects, in mean CD4 + T-cell count change (278 vs 250 cells/μL, P = .474) or CD4/CD8 ratio change (0.30 vs 0.32, P = .854). Similarly, we did not detect differences between treatment arms in secondary endpoints. Conclusions: In HIV-infected patients initiating ART at advanced disease, the clear immunological benefits of ART were not enhanced by this nutritional intervention targeting the gut-associated lymphoid tissue and microbiota. Clinical Trials Registration: NCT00870363.